Profitabilitas, Harga Saham dan Ukuran Perusahaan Sebagai Variabel Moderasi - Pramudya, Wisnu Haryo; Herutono, Slamet; Kapti, Ani Sri Murwani Kumoro (E-Jurnal Akuntansi, 2022)
This study aims to test whether profitability has an effect on stock prices and test whether firm size affects profitability on stock prices. This study uses the independent variable profitability with ROA as a proxy, the dependent variable is stock price and the moderating variable is the size of the company as a proxy for total assets. Moderated regression analysis is a tool that will be used to analyze the proposed hypothesis. The population used is all contractors and real estate companies listed on the IDX from 2018 to 2020. The method used to take samples is purposive sampling. The results of the analysis of this study can prove that the hypothesis built is that profitability has an effect on stock prices and firm size moderates the effect of profitability on stock prices. Keywords: Profitability; Stock Price; Company Size.